(untitled) (Journal of Medical & Health Sciences Review, 2025)
Psilocybin, MDMA, and LSD have recently emerged as popular psychedelic substances for use in psychopharmacology in managing various disorders including treatment-resistant depression, PTSD, and anxiety. These substances mainly affect the serotonergic receptors that involve the regulation of consciousness, perceptions, and cognition. These unique alterations in brain connectome show the influence of psilocybin and LSD on neuroplasticity and DMN, therefore supporting the sustained improvement in depressive symptoms and existential anxiety. MDMA, as compared to classical psychedelics, evokes positive changes in emotional processing and reduction of specific fear in PTSD patients. Scientific trials show that the problem can abate after several recurrences after a few sessions, unlike the cases of traditional antidepressants where constant use is necessary. However, there are some shortcomings, like legal regulation, ethical issues, and possible negative impacts, including temporary increased anxiety and cardiovascular issues. This paper aims to analyze the neurobiological effects and therapeutic efficacy of psychedelics along with their legal contexts in the context of modern psychiatry, stressing the importance of future research, policy changes, and a rational clinical prescription of psychedelics for their maximal beneficial impact on mental health.